Trust contributing factors in mobile learning among Universiti Teknologi MARA students / Norazlinawati Walid - Walid, Norazlinawati (2012)
The use of m-learning is gaining attention. However, trustworthy towards the effectiveness of the learning sessions using m-learning is still questioned such asthe accuracy, validity and understandable of information disseminate. Therefore, this research focuseson trust contributing factors in m-learning among Universiti Teknologi MARA (UiTM)students to deep in this issue. Three components of factors concerned which are demographic, build trust and sustain trust factors. Two models are adapted and modified which are ‘Build Trust in Learning Network Framework’ and ‘Derived Trust Building Framework’. 19 trust factors and seven demographic factors were used as variable. Data collected using self-administrated survey. Usable questionnaire were analyzed using descriptive analysis and inferential analysis. For model testing,a Structural Equation Modeling (SEM) method was adopted. The findings of this researchshows that the m-learning users among UiTM students that are more trustable the m-learning are ‘male’,’28-38’ years old, from ‘main campus’, ‘part time students’, period of using was more than five years, frequency of using is ‘everyday’ and the iPhone users. Meanwhile,thetrust factors that able to influence users to trust them-learning in descending order based on percentage are ‘Familiarity’, ‘Information Quality’, ‘Interaction’, ‘Feasibility’, ‘Goal Setting’, ‘3rd Party Recognition’, ‘Attractive Reward’, and ‘Rules’ to build the trust; and ‘Consistency’, ‘Reliability’, ‘Experience Sharing’, ‘Integrity’, ‘Security Control’, ‘Community Building’, ‘Open Communication’, ‘Site Quality’, ‘Feedback’, ‘Time’, and ‘External Auditing’ to sustain the trust.However, from the EFA result it collective the factors into System Ability, Policy Setting, System Functionality, and Incentive Program as Build Trust Factors; and Security, Information Reliability, Feedback, Added-Value, Open Communication, and Experience Sharing as the Sustain Trust Factors. But, from the model testing result, it was suggested that both model need some modification.